A MORPHOLOGICAL ANALYSIS OF DERIVATIONAL SUFFIXES IN PSYCHOLOGICAL CONTENT - Septika Ariyanti; Abdur Rahman (Aisyah Journal of English Language Teaching (AIJELT), 2023)
The objective of current study is to analyze the used of derivational suffixes in psychological content of Psych2go youtube channel. Affixes and roots are combined through the derivational process to produce new words. Derivation is thought of as the creation of new words out of already existent ones (Rahayu, 2019). The main morphological element utilized to create new words from pre-existing words is a suffix. The method used in this research is descrptive method and qualitative analysis. The data was taken from Psych2go youtube channel with the video entitled “3 Daily Rituals for Better Mental Health”. The result of this research revealed that there are 9 suffixes used in the content namely suffix –ly, -ful, -ness, -ion, -al, -ance/-ence, -ity, -ish, -able. The researcher makes this recommendation to other researchers who have an interest in analyzing and who wish to have a thorough comprehension of the numerous suffix kinds in YouTube channel content.